Calibration Results for Non-Expected Utility Theories - Safra, Zvi; Segal, Uzi (Econometrica, 2008)
Rabin (2000) proved that a low level of risk aversion with respect to small gambles leads to a high, and absurd, level of risk aversion with respect to large gambles. Rabin's arguments strongly depend on expected utility theory, but we show that similar arguments apply to general non-expected utility theories.